Circular dichroism and magnetic circular dichroism spectroscopy for organic chemists - Kobayashi, Nagao (Royal Society of Chemistry, 2011)
CD and MCD spectroscopy can provide key information about the conformations and electronic states of chromophore containing molecules. However, the theory has remained too challenging and inaccessible for many organic chemists and biochemists and only a few researchers have carried out detailed quantitative analyses of their spectral data. This is not surprising as people who excel at spectroscopic theory usually lack the skills set required to design and synthesise the molecules that would be most appropriate for describing and explaining the theory of CD and MCD spectroscopy. Most of the books that have been written on the subject have, therefore, been based on very dense sets of mathematical equations. This timely book rectifies that situation by summarizing the relationship between the different types of spectra and by describing in detail the qualitative and quantitative methods which can readily be used to analyse CD and MCD spectral data. During the last decade the authors have successfully synthesized several molecules to illustrate key points related to the theory of CD and MCD spectroscopy, resulting in this definitive book providing key practical knowledge in a readily accessible style. It is aimed primarily at organic chemists and biochemists and is required reading for researchers active in the field. In the introduction, the book describes the types of information that can be derived from CD and MCD spectroscopy. After a detailed explanation of the theory of electronic absorption spectroscopy, it then provides practical in depth examples of the various analytical methods that can be carried out with CD and MCD spectral data. This makes the theory of these techniques much more accessible for researchers who do not specialise in physical chemistry. The book concludes by briefly summarizing the key mathematical expressions associated with each technique.